Pengaruh Pemberian Penghargaan, Kecerdasan Spiritual dan Motivasi Kerja terhadap Kinerja Guru Pendidikan Agama Hindu pada SMA/SMK Bersertifikat Pendidik di Kabupaten Buleleng - Wardhani, Ni Ketut Sri Kusuma; Mahendradhani, Gusti Ayu Agung Riesa; Pramasanti , Desak Ketut (Jayapangus Press, 2025)
Rewarding is one strategy that has been proven effective in increasing work motivation. Rewards can be in the form of verbal appreciation, formal awards, or financial incentives, all of which positively impact motivation. Teachers with high spiritual intelligence tend to deal with pressure and challenges in their work better. This study aims to describe and test the influence of each variable, both direct and indirect relationships of reward, spiritual intelligence, and work motivation, on the performance of Hindu religious education teachers who are certified educators in SMA-SMK Buleleng Regency. This study uses a descriptive-correlational research design. The population of this study was 37 teachers with a total sampling technique. Data analysis used path analysis. The study found that, (1) Descriptively, rewarding is classified as good, teachers' spiritual intelligence is classified as high, and teacher performance is in a good category; (2) Rewarding contributes 25.8% to work motivation; (3) Spiritual Intelligence contributes 15.6% to work motivation, (4) Rewarding contributes around 27.25% to teacher performance; (5) Spiritual Intelligence contributes around 34.35% to teacher performance, (6) The indirect effect of giving awards on teacher performance through work motivation is 19.74% of the total model and (7) The indirect effect of spiritual intelligence on teacher performance through work motivation is 15.35% of the total model. Based on these findings, teacher performance can be formed through giving good awards, spiritual intelligence, and high work motivation.